The Difference in Prognosis between Renal Sinus Fat and Perinephric Fat Invasion for pT3a Renal Cell Carcinoma: A Meta-Analysis. - Zhiling Zhang; Chunping Yu; Liliya Velet; Yonghong Li; Lijuan Jiang; Fangjian Zhou (PLoS ONE, 2016)
In the current Tumour-Node-Metastasis (TNM) classification system for renal cell carcinoma (RCC), both renal sinus fat invasion (SFI) and perinephric fat invasion (PFI) are defined as T3a, suggesting that the prognosis should be similar for the two pathologic findings. Several studies, however, have reported a worse prognosis for SFI in patients with a T3a tumor. In order to compare the prognosis of these two pathologic findings (SFI versus. PFI) in a more comprehensive way, this meta-analysis was performed.To identify relevant studies, Medline, Embase, Cochrane Library, and Scopus database were searched from the inception until October 2014. A meta-analysis was performed using Review Manager 5.2 and STATA 11. Pooled Odds ratio (OR) and/or hazard ratio (HR) with 95% confidence interval (CI) were calculated to examine the risk or hazard association.A total of 6 studies including 1031 patients qualified for analysis. T3a RCC patients with SFI were significantly associated with poor cancer specific survival(CSS) (HR: 1.47, 95% CI: 1.19-1.83; P<0.001) compared to those with PFI. In T3aNx/N0M0 subgroup, SFI patients also showed a worse prognosis than those with PFI (CSS, HR: 1.94, 95% CI: 1.21-3.12; P = 0.006). T3a RCC patients with SFI had higher Furhman grade, greater possibility of lymph node metastasis, sarcomatoid differentiation and tumour necrosis. Main limitation is the relatively small number of included studies.The present meta-analysis suggested that SFI is associated with worse CSS in patients with pT3a RCC. However, due to the small number of included studies, future studies with a large sample size are required to further verify our findings.